Effectiveness of Health Promotion Using the Snakes and Ladders-Hopscotch Game Media on Adolescent Knowledge of Vegetable and Fruit Consumption at SMPN 6 Jambi City - Irma Handayani; Asrial Asrial; Ummi Kalsum; Haryanto Haryanto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Vegetable and fruit consumption among adolescents aged 10–14 years remains very low at 2.3%. Adolescents prefer fast food, often neglecting their need for vegetables and fruits, even though a balanced diet is crucial for their growth and development. This study aims to analyze the effectiveness of a Snakes and Ladders game combined with hopscotch in increasing adolescents' knowledge about vegetable and fruit consumption. The research used a quasi-experimental design with a two-group pre-test-post-test approach at SMPN 6 and SMPN 11 in Jambi City, with a sample of 52 respondents in the intervention group and 51 in the control group. Data analysis was performed using the Wilcoxon and Mann-Whitney tests. The Wilcoxon test showed a significant increase in knowledge in the intervention group (p=0.000), whereas the control group showed no significant change (p=0.257). The results of the Mann-Whitney test also showed no significant difference between the two groups at pre-test (knowledge p=0.628). Still, after the intervention, there was a significant difference in knowledge (p=0.000). The hopscotch, snakes, and ladders game is effective at increasing adolescents' knowledge about vegetable and fruit consumption. This media is recommended for use in health education in schools and healthcare facilities Keywords:  Model,  Snakes and Ladders Media, Hopscotch,  Fruit and Vegetable Consumption,  Adolescents